On the relationship between objective and subjective social indicators: implications for social planning in Ireland - Davis, E. E.; Fine-Davis, Margaret (Statistical and Social Inquiry Society of Ireland, 1979)
This paper, while recognising the importance of objective social indicators for social planning, makes a case for the addition of subjective social indicators as a necessary complement. Furthermore, it is argued that objective social indicators based on aggregate statistics for the country as a whole, even when these are disaggregated to a certain extent, cannot yield the same type of information obtainable through the use of sample survey techniques of the kind used in the present study, which enable the collection of both objective and subjective social indicator data on the same individuals. The value of this technique of relating objective and subjective social indicators is illustrated on the basis of selected findings from the 1977 Continuing Social Survey carried out in Ireland on a nationwide representative sample of just over 2,000 individuals drawn from the Electoral Register. The major portion of this questionnaire consisted of an EEC-wide harmonised study relating to the areas of health, health services, housing, the environment and life in general. This is the first in a series of such studies sponsored by the Statistical Office of the European Communities, Luxembourg, which are seen in the social action program of the Community as "a means of facilitating and encouraging the progressive convergence of social conditions in the Community, and of providing an essential basis for Community decisions concerning common targets in the social field". In addition to analysing in greater detail the Irish data of the EEC harmonised portion of the questionnaire, the Continuing Social Survey in Ireland consists of a second portion specific to social problems in Ireland and designed to make a further input to social planning.
Read before the Society, 8 March 1979
Keywords: Objective social indicators; Subjective social indicators; Social planning in Ireland; 314.15